Sweet corn (Zea mays L.) seed germination and production under water and nitrogen deficit under glasshouse conditions - Shahriari, Ali (2013)
Water and nitrogen deficits limit plant performance and subsequently reduce the yield potential in corn. The effect of osmotic potentials (MPa) on sweet corn was evaluated during seed germination in the laboratory and the effects of water and different nitrogen rates were evaluated under field conditions. Seeds of eight sweet corn varieties (Hybrid 968, Hybrid 969, Hybrid 926, Hybrid 8800, Hybrid 3922, Hybrid 2328, Masmadu and Thai Super Sweet) were germinated in Petri dishes containing polyethylene glycol (PEG) at concentrations equivalent to -0.2, -0.5, -0.7, 1.2 and -1.4 MPa osmotic potential. The results showed that proline content in the seedling and mean germination time increased with increasing osmotic potential. However, germination percentage (GP), germination index (GI), coefficient of velocity of germination (CVG), root length (RL) and root diameter (RD) were reduced with increasing osmotic potential. Two hybrids of sweet corn, hybrid 968 and 926, were subsequently planted under rain shelter and water deficits were imposed at vegetative, tasseling and both at vegetative and tasseling stages, with nitrogen rates at 40, 120 and 200 kg ha-1. The reproductive growth stage was more sensitive to water deficit and reduced nitrogen rates compared with the vegetative growth stage for all varieties. Water and nitrogen deficit during vegetative and reproductive growth stages reduced ear size (ES), kernel weight per ear (KWE), number of kernel per ear (NKE) and 1000 -kernel weight (1000-KW). The number of rows per ear (RE) was affected under nitrogen deficit. Water deficit and nitrogen rates of less than200 kg/ha, at both vegetative and reproductive stages, reduced plant height, number of leaves, leaf area index (LAI), crop growth rate (CGR), chlorophyll content and dry matter. Relative water content, photosynthesis rate and stomatal conductivity values were significantly influenced under water deficit and nitrogen deficit. Pollen number was reduced when plants were imposed to water and nitrogen deficit. However, pollen viability was only affected under water deficit. Water deficit for short periods did not affect shoot nitrogen concentration, but nitrogen concentration in shoot was reduced under nitrogen deficit. The study indicated that proline content in seedling was increased when germination occur at low osmotic potentials. Ear weight m-² under adequate moisture conditions needs higher nitrogen to produce optimum yield than under stress conditions. Therefore, sweet corn varieties under vegetative drought require 120 kg ha-1of applied nitrogen to obtain optimum seed yield.